2018
DOI: 10.1080/10400435.2018.1463575
|View full text |Cite
|
Sign up to set email alerts
|

iPads/tablets and students with autism: A meta-analysis of academic effects

Abstract: Since the introduction of iPads in 2010, educators have been working to effectively incorporate this technology as a supplement to curriculum and a tool to increase student engagement and student achievement. The current investigation examines the effectiveness of iPad applications in supporting the instruction of students identified on the autism spectrum. Specifically, this investigation provides a meta-analysis of available research that examines the use of iPad technology and its impact on learning outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
1
11
0
4
Order By: Relevance
“…The metaanalysis on academic effects conducted by Aspiranti et al's (2020) among ASD learners showed positive results. It is suggested that the use of iPads in the classroom "have a positive impact on student achievement for students with autism, when incorporated as part of their daily learning experiences" (Aspiranti et al, 2020, p. 29). Valencia et al's (2019's systematic review revealed that the use of virtual agents, artificial intelligence, virtual reality, and augmented reality offers alternative learning environments for learners on the autism spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…The metaanalysis on academic effects conducted by Aspiranti et al's (2020) among ASD learners showed positive results. It is suggested that the use of iPads in the classroom "have a positive impact on student achievement for students with autism, when incorporated as part of their daily learning experiences" (Aspiranti et al, 2020, p. 29). Valencia et al's (2019's systematic review revealed that the use of virtual agents, artificial intelligence, virtual reality, and augmented reality offers alternative learning environments for learners on the autism spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…This rapid increase can be attributed to several reasons such as commercial interests such as license fees for graphic symbols; increased awareness of the utility of graphic symbols for communication (Isaacson and Lloyd, 2013;McNaughton and Light, 2015) and educational purposes (Mavrou et al, 2013); an explosion of use of graphic symbols (e.g. emojis), for communication purposes by the general community for use in social media such as Facebook and Instagram (Weissman and Tanner, 2018); the advancement of mobile technology (Bunning et al, 2012;Aspiranti et al, 2020) and developments occurring in the world of artificial intelligence (AI) with its impact on AAC where machine learning, natural language processing and image recognition are all changing the way symbol systems are developed and used.…”
Section: Toward a New Classification Of Aac Symbolsmentioning
confidence: 99%
“…Although one of the students showed a lower improvement than his peers, he still preferred using a tablet-device (Moreno, 2020). A meta-analysis of studies that explored the use of touchscreen devices concluded that using tablets as a supplementary tool has a significant effect on students' math and reading skills (Aspiranti, Larwin, & Schade, 2020).…”
Section: Use Of Tablet Pcs In Education For Children With Sendmentioning
confidence: 99%